THE EFFECTIVENESS OF USING STATION ROTATION MODEL TO IMPROVE STUDENTS’ READING SKILL IN RECOUNT TEXT (A Quasi Experimental Research at the Tenth Grade Students of MA NU Mu’allimat Kudus) - Izzatin Nisa (Universitas Islam Nahdlatul Ulama Jepara, 2018)
The objective of this research is to find the effectiveness of using Station Rotation model to improve students’ reading skill achievement, especially for recount text at the tenth grade students of MA NU Mu’allimat Kudus academic year 2017/2018. The subjects of this research were 80 students. Experimental research was used as a method in this research. The research was conducted in two group, they are the experimental group and the control group. The experimental group was students which were taught by Station Rotation model, while the control group was students which were taught without Station Rotation model. The data were gathered through tests which were delivered into the pre-test and the post-test. The result of the research showed that Station Rotation model is effective to use in teaching reading skill in recount text. Gained score of the experimental group (19.7) is higher than the control group (9.6). From the result of statistic calculation, it was obtained that the value of t-observation (to) is 3.97 and degree of freedom (df) is 78. In the table of significance 5%, the value of degree of significance is 1.99. Comparing those values, the result is 3.97 > 1.99 which means t-observation (to) score is higher that t-table (tt) score. In other words, the Alternative Hypothesis (Ha) is accepted and the Null Hypothesis (Ho) is rejected. Therefore, teaching reading skill in recount text by using Station Rotation model is effective.